The intramembrane protease SPPL2c promotes male germ cell development by cleaving phospholamban. (7th February 2019) - Niemeyer, Johannes; Mentrup, Torben; Heidasch, Ronny; Müller, Stephan A; Biswas, Uddipta; Meyer, Rieke; Papadopoulou, Alkmini A; Dederer, Verena; Haug‐Kröper, Martina; Adamski, Vivian; Lüllmann‐Rauch, Renate; Bergmann, Martin; et al.
Abstract: Signal peptide peptidase (SPP) and the four homologous SPP‐like (SPPL) proteases constitute a family of intramembrane aspartyl proteases with selectivity for type II‐oriented transmembrane segments. Here, we analyse the physiological function of the orphan protease SPPL2c, previously considered to represent a non‐expressed pseudogene. We demonstrate proteolytic activity of SPPL2c towards selected tail‐anchored proteins. Despite shared ER localisation, SPPL2c and SPP exhibit distinct, though partially overlapping substrate spectra and inhibitory profiles, and are organised in different high molecular weight complexes. Interestingly, SPPL2c is specifically expressed in murine and human testis where it is primarily localised in spermatids. In mice, SPPL2c deficiency leads to a partial loss of elongated spermatids and reduced motility of mature spermatozoa, but preserved fertility. However, matings of male and female SPPL2c −/− mice exhibit reduced litter sizes. Using proteomics we identify the sarco/endoplasmic reticulum Ca 2+ ‐ATPase (SERCA2)‐regulating protein phospholamban (PLN) as a physiological SPPL2c substrate. Accumulation of PLN correlates with a decrease in intracellular Ca 2+ levels in elongated spermatids that likely contribute to the compromised male germ cell differentiation and function of SPPL2c −/− mice. Synopsis: The intramembrane protease SPPL2c is critical for the turnover of selected tail‐anchored proteins in spermatids and thereby supports differentiation and function of male germ cells. The presenilin‐homologue Signal peptide peptidase‐like 2c is an ER‐resident intramembrane protease endogenously expressed in murine and human spermatids. SPPL2c processes selected tail‐anchored proteins with a substrate spectrum distinct from that of Signal peptide peptidase (SPP). SPPL2c‐deficient mice show a partial loss of elongated spermatids and reduced motility of mature spermatozoa. Phospholamban represents a physiological SPPL2c substrate in murine testis. Abstract : The intramembrane protease SPPL2c is critical for the turnover of selected tail‐anchored proteins in spermatids and thereby supports differentiation and function of male germ cells.